Preliminary results from prebiotic molecules with ALMA in the era of artificial intelligence. Issue Volume 15:Issue S352(2019) (June 2019) - Villicana-Pedraza, I.; Walterbos, R.; Carreto-Parra, F.; Ott., J.; Momjian, E.; Thelen, A.; Ginsburg, A.; Zapata, L.; Gonzalez, M.; Floyd, J.; Saucedo, J.; Binette, L.; et al.
Abstract: Study of the composition from diverse sources of the Universe helps to us to understand their evolution. Molecular spectroscopy provides detailed information of the observed objects. We present a small study of the starburst NGC 253 with ALMA at 1mm. We detect the prebiotic molecules NH2 CHO, and CNCHO. We obtain the integrated intensity maps and abundances of HNCO, CH3 OH, H3 O+ and CH3 C2 H. We propose the use of Artificial Intelligence for big data to find prebiotic molecules in galaxies.